Intellectual Capital and Green Accounting on the Performance of Industrial Sector Companies in 2022-2024 (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to empirically analyze the influence of intellectual capital and green accounting on the Company's performance. The importance of intangible resource management and compliance with environmental responsibility in creating a competitive advantage and the sustainability of the company's operations, especially during post-pandemic industrial dynamics. The phenomenon of declining Return on Assets (ROA) in several industrial sector companies also encourages the need to evaluate the effectiveness of the managerial strategies implemented. This study uses a quantitative approach with multiple linear regression analysis techniques. Samples were selected from 21 industrial sector companies that consistently published annual and sustainability reports during the study period. Secondary data is obtained from financial statements, sustainability reports, and official sources such as the IDX. The results of this study are expected to provide empirical evidence regarding the extent of the strategic role of intellectual capital and green accounting practices in increasing company efficiency, profitability, and legitimacy.